Alexander Hamilton : founding father and statesman - Haugen, Brenda (Compass Point Books, 2005)
Presents a biography of Alexander Hamilton, the United States' first secretary of the treasury, discussing his early life and education, his military service during the American Revolution, and his role in forming the government of the new nation.